Parkinson's Disease With Visual Hallucinations Is Associated With Epileptiform Activity on EEG - Fry, Adam; Singh, Dharampreet; Manganas, Louis; Gordon, Marc L.; Christodoulou, Christopher; Leung, Hoi-Chung; Schwartz, Guy J. (Frontiers in Neurology, 2022)
ABSTRACT Background: Visual hallucinations (VHs) in Parkinson’s disease (PD) are the cardinal symptoms which declare the onset of PD psychosis (PDP). The anthropomorphic and zoomorphic VHs of PD resemble those of Charles Bonnet syndrome and temporal lobe epilepsy. In both of these disorders electroencephalography (EEG) abnormalities have been described. We therefore sought to examine whether VHs in PD were associated with similar EEG abnormalities. Methods: This retrospective observational study searched the medical records of 300 PD patients and filtered for those containing clinical 20-minute scalp EEGs. Remaining records were separated into two groups: patients with reported VHs and those without. The prevalence of epileptiform discharges in the EEGs of both groups was identified. Results: Epileptiform discharges were present in 5 of 13 (38.5%) PD patients with VHs; all localized to the temporal lobe. No epileptiform discharges were observed in the EEGs of the 31 PD patients without VHs. Conclusion: The significantly high incidence of temporal lobe epileptiform discharges in PD patients with VHs as compared to those without VHs lends to the possibility of an association visual cortex epileptogenic focus. Accordingly, for treatment-refractory patients, antiepileptic drugs might be considered, as in the case of Charles Bonnet syndrome, temporal lobe epilepsy and migraine with visual aura. Future prospective studies involving larger samples and multi-center cohorts are required to validate these observational findings.